Determinan Manajemen Pajak pada Perusahaan Manufaktur di Bursa Efek Indonesia: Pengaruh Profitabilitas, Intensitas Aset Tetap, dan Leverage - Ester Tesalonika Manri; Juaniva Sidharta; Melinda Malau (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze and obtain empirical evidence regarding the influence of Profitability, Fixed Asset Intensity, and Leverage on Tax Management in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sample selection was carried out using a purposive sampling method, resulting in 44 companies with a total of 220 observation data points during the observation period. The data analysis method used in this study is multiple linear regression analysis with the help of SPSS 29 software. Before testing the hypothesis, the regression model was tested for its feasibility through a series of classical assumption tests. The results of the heteroscedasticity test using the Glejser Test method show that the variables Profitability (Sig. 0.160), Fixed Asset Intensity (Sig. 0.294), and Leverage (Sig. 0.994) have significance values greater than 0.05, indicating that the model is free from heteroscedasticity symptoms. Furthermore, the results of the autocorrelation test using the Durbin-Watson method produced a calculated value of 1.720, which indicates that the regression model is in ideal conditions and meets the requirements of classical assumptions. The implications of this research are expected to contribute to company management in formulating effective tax strategies by considering asset structure and debt ratios. Additionally, the results of this study can serve as evaluation material for tax authorities in tightening tax compliance supervision in the manufacturing sector, as well as serve as an academic reference for future researchers.